1998
DOI: 10.1111/j.1460-9568.1998.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Cells in laminae III and IV of the rat spinal cord which possess the neurokinin‐1 receptor receive monosynaptic input from myelinated primary afferents

Abstract: We have previously demonstrated that neurons which have cell bodies in laminae III or IV of the rat spinal cord, dendrites that enter the superficial laminae and which possess the neurokinin-1 receptor receive a major synaptic input from substance P-containing primary afferent axons. In this study we set out to determine whether these cells also receive monosynaptic input from myelinated primary afferents by using transganglionic transport of the B subunit of cholera toxin to identify the central terminals of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…1 A). As described previously, these cells also often had dendrites that remained in the deeper laminae (Brown et al, 1995;Naim et al, 1997Naim et al, , 1998. The distribution of N PY immunoreactivity was also the same as that reported in previous studies in the rat (Hökfelt et al, 1981;Hunt et al, 1981;Sasek and Elde, 1985;Rowan et al, 1993): a dense plexus of N PY-immunoreactive axons was observed in laminae I and II ( Fig.…”
Section: Confocal Microscopysupporting
confidence: 87%
See 3 more Smart Citations
“…1 A). As described previously, these cells also often had dendrites that remained in the deeper laminae (Brown et al, 1995;Naim et al, 1997Naim et al, , 1998. The distribution of N PY immunoreactivity was also the same as that reported in previous studies in the rat (Hökfelt et al, 1981;Hunt et al, 1981;Sasek and Elde, 1985;Rowan et al, 1993): a dense plexus of N PY-immunoreactive axons was observed in laminae I and II ( Fig.…”
Section: Confocal Microscopysupporting
confidence: 87%
“…Sections were examined with a Bio-Rad (Hemel Hempstead, UK) MRC 1024 confocal scanning laser microscope with a Krypton-Argon laser (Naim et al, 1997(Naim et al, , 1998. N K1 receptor-immunoreactive neurons with cell bodies located Ͼ150 m below the dorsal white matter (in lamina III or IV) and dendrites that could be traced into lamina II were selected for f urther study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Morphologically, they receive limited myelinated afferent input as well as dense innervation from substance P-containing primary afferents in lamina I/II. They have been likened to wide dynamic range neurons (Naim et al, 1997(Naim et al, , 1998) and project to the brainstem (Todd et al, 2000) and thalamus (Marshall et al, 1996). The other subgroup of lamina III/IV, NK1Rϩ neurons have more restricted dendritic trees.…”
Section: Primary Afferent Inputmentioning
confidence: 99%